TIME VALUE OF MONEY SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI MODERN: Analisis Literatur Pada Real Aset, Pasar Uang, Dan Securities Crowdfunding - Putri Hayati; Sabrina Faraditha; Putri Anggraini; Pebriansyah Siregar; Rahman Saleh Nasution; Danu Wijaya; Muhammad Ikhsan Harahap (CV. Barokah Publsiher, 2025)
This study aims to analyze the application of the Time Value of Money (TVM) concept across three major investment categories—money market instruments, real assets, and securities crowdfunding—by emphasizing how the principle of time-based value shapes the evaluation of risk, feasibility, and the real value of investment returns. Using data on policy interest rates, inflation levels, residential property price growth, rental yields, money market mutual fund performance, and the return–default ratio within the crowdfunding industry, this study demonstrates that TVM plays a crucial role in determining whether an investment can generate positive real value for investors. In the money market, TVM helps assess whether relatively low returns can withstand inflationary pressures and high benchmark interest rates; in real assets, it measures the long-term viability of rental income and capital gains amid moderate property price growth; and in crowdfunding, it becomes essential for evaluating uncertain cash flows and higher risks despite attractive nominal returns. The findings affirm that TVM is not merely a theoretical concept but a practical foundation necessary for making objective, rational, and measurable investment decisions within the dynamics of the modern economy.